Optimalisasi Woman Enterpreneur melalui Pemanfaatan Jejaring Pemasaran dan Social Media Marketing - Ari Muhardono; Danang Satrio; Zahro Zahro; Ina Rotul Mila (Universitas Pahlawan Tuanku Tambusai, 2022)
The Covid-19 pandemic has had a drastic impact on the Indonesian economy, with economic conditions in decline, millions of Indonesians are at risk of losing their jobs. This has given rise to many new female entrepreneurs who started their businesses during the Covid-19 pandemic. The Aisyiyah Entrepreneurial School, Doro District, Pekalongan Regency is a forum for empowering women through education and business assistance. The lack of knowledge and skills of female entrepreneurs regarding effective product marketing strategies makes it difficult for their businesses to develop, especially in the current pandemic era. Therefore, training and marketing literacy assistance are needed for women entrepreneurs to be able to compete and be innovative to increase sales turnover in the pandemic era. The results of the activity have a significant impact, motivate and add insight to female entrepreneurs, especially small and medium business actors in Doro District, Pekalongan Regency, regarding digital marketing strategies both in terms of knowledge and practice. so that they can develop their business through digital marketing.